Enhancing Neurosteroid Synthesis – Relationship to the Pharmacology of Translocator Protein (18 kDa) (TSPO) Ligands and Benzodiazepines - Wolf, L.; Bauer, A.; Melchner, D.; Hallof-Buestrich, H.; Stoertebecker, P.; Haen, E.; Kreutz, M.; Sarubin, N.; Milenkovic, V. M.; Wetzel, C. H.; Rupprecht, R.; Nothdurfter, C. (Pharmacopsychiatry, 2015)
Introduction: The treatment of anxiety disorders is still a challenge; novel pharmacological approaches that combine rapid anxiolytic efficacy with fewer side effects are needed. A promising target for such compounds is the mitochondrial translocator protein (18 kDa) (TSPO). TSPO plays an important role for the synthesis of neurosteroids, known to modulate GABAA receptors, thereby exerting anxiolytic effects.Methods: We investigated the pharmacological profile of 2 well established TSPO ligands (XBD173 and etifoxine) compared to the benzodiazepine diazepam with regard to TSPO binding affinity, TSPO expression and neurosteroidogenesis.Results: In BV-2 microglia and C6 glioma cells all compounds significantly enhanced TSPO protein expression. Radioligand binding assays revealed the highest binding affinity to TSPO for XBD173, followed by diazepam and etifoxine. Pregnenolone synthesis was most potently enhanced by etifoxine.Discussion: Etifoxine turned out to be the most potent enhancer of neurosteroidogenesis, although its binding affinity to TSPO was lowest. These results indicate that the efficacy of TSPO ligands to stimulate neurosteroid synthesis, thereby leading to anxiolytic effects cannot be concluded from their binding affinity to TSPO.
Keywords: TSPO ligands; benzodiazepines; pregnenolone; neurosteroids; anxiolytic